Exploring Capital Structure Determinants for OECD Energy Firms - Zandi, Gholamreza; Rehan, Raja; Adnan Hye, Qazi Muhammad; Bee Choo, Sandy Low (International Journal of Energy Economics and Policy, 2023)
Energy is considered as a critical factor for supporting Economic Co-operation and Development (OECD) countries’ economic growth. However, little is known about OECD-based energy firms’ capital structure determinants. Hence, this investigation is an effort to explore the capital structure determinants for OECD countries’ energy firms. In this context, 18 key OECD countries 43 energy firms are selected. The balanced panel data sample set of 14 years from 2007 to 2020 is constructed to perform empirical analysis. The eight selected determinants, which are tangibility, current ratio, non-debt tax shield, return on equity, annual gross domestic product, inflation, and energy consumption are examined in association with capital structure that is measured by debt-to-asset ratio. By engaging a Panel Data Static Model and Dynamic Model via Generalized Method of Moments (GMM), the outcomes expose that tangibility, profitability, gross domestic product, energy consumption, and lagged dependent variable are the key capital structure determinants for energy firms of OECD countries. Notably, the significant role of a lagged dependent variable specifies the existence of a dynamic capital structure and speed of adjustment for these firms. Also, the significant role of tangibility directly indicates the relevance of the Dynamic Trade-Off theory. The findings pave new ways for policymakers to develop similar policies that will enhance collaboration in OECD countries to knob forth seeing energy-connected issues. Likewise, the identification of key determinants will also be helpful for these firms to construct best mix of debt and equity that ultimately enhance their financial performance and market value.